2003
DOI: 10.1530/eje.0.1490209
|View full text |Cite
|
Sign up to set email alerts
|

Hypercalciuria is a common and important finding in postmenopausal women with osteoporosis

Abstract: Objective and design: The prevalence and the effects of hypercalciuria on bone in patients with primary osteoporosis are poorly defined. We therefore retrospectively analyzed the data of 241 otherwise healthy women. They were 45-88 years of age and had been referred for their first visit to our Unit for Metabolic Bone Diseases over a 2-year period because of primary osteoporosis (bone density T-score , 22.5). Methods: The main parameters of calcium and skeletal metabolism had been analyzed in all subjects. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
46
0
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(52 citation statements)
references
References 21 publications
4
46
0
2
Order By: Relevance
“…Several studies demonstrated that IH in childhood is associated with low BMD (31,32), suggesting that life-long hypercalciuria may compromise bone health and increase fracture risk. In addition, studies in postmenopausal women with primary osteoporosis have reported a 10%-19% prevalence of hypercalciuria (33,34).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies demonstrated that IH in childhood is associated with low BMD (31,32), suggesting that life-long hypercalciuria may compromise bone health and increase fracture risk. In addition, studies in postmenopausal women with primary osteoporosis have reported a 10%-19% prevalence of hypercalciuria (33,34).…”
Section: Discussionmentioning
confidence: 99%
“…[16] This can account for the differences between this study and that of Shiarishi et al [17] This loss of calcium is, nevertheless, important, as hypercalciuria is one of the most common features of postmenopausal bone loss with osteoporosis in 50% of patients. [18,19] As the name refers, bone mineral density is a measure of the mineral content of a bone or specific region of a bone and, therefore, it indicates a measure of strength of a bone. In the present study, the diameters of the tibial head and shaft were significantly reduced in the unsupplemented Ovx group.…”
Section: Discussionmentioning
confidence: 99%
“…Neste estudo, a HC esteve presente em 15% das pacientes analisadas, valor este semelhante a alguns estudos (4,5), porém superior ao trabalho de Tannenbaum e cols., que encontraram uma incidência de 10% (7). Alguns autores demonstraram correlação negativa entre a HC e a densidade óssea, ou seja, quanto maior a HC menor a DMO (4).…”
Section: Discussionunclassified
“…Além disso, Giannini e cols. mostraram que a hipercalciúria foi um fator significativo na redução da massa óssea (5).…”
Section: Hipercalciúria Na Osteoporoseunclassified